Valorização dos compostos terpênicos via catálise por heteropoliácidos: isomerização de compostos terpênicos e síntese do florol - Augusto Luis Pereira de Meireles (2017)
Terpenes are found in nature in essential oils of plant materials, often as main constituents. Terpenes and their synthetic derivatives represent an important renewable feedstock for perfumery, pharmaceutical and cosmetic industries. Various useful terpenoid products are industrially produced through the acid catalyzed transformations of more abundant terpenes. Heteropoly acids (HPAs) of the Keggin series are widely recognized as attractive acid catalysts for the green synthesis of many fine and specialty chemicals for important processes in fine chemistry due to the strong Brønsted acidity and high chemical stability. Supported HPAs can be used as heterogeneous catalysts in non-polar and weakly polar media without leaching problems. On the other hand, for heterogeneous catalysis in polar solvents, where HPAs are highly soluble, their insoluble acidic salts represent excellent alternative. In particular, Cs2.5H0.5PW12O40 (CsPW), a compound with strong Brønsted acidity and large surface area, can be used as a heterogeneous acid catalyst in polar media. Even from homogeneous systems HPAs can be recovered and recycled without neutralization by precipitating with a non-polar solvent. The H3PW12O40 is a homogeneous catalyst for the synthesis of -bisabolol, a high-priced and highly demanded ingredient for the fragrance, cosmetic and pharmaceutical industries, starting from more abundant biomass-based sesquiterpenic alcohols. In acetone solutions, -bisabolol can be obtained in 5560% yields from nerolidol and 6070% yields from farnesol at complete substrate conversions. -bisabolol synthesized by this method contains no farnesol, which is a potentially allergenic compound and should be avoided in the commercially used -bisabolol. The catalyst shows high turnover numbers and operates under mild nearly ambient conditions. The isomerization of caryophyllene oxide, one of the most widespread sesquiterpenes found in various essential oils, catalyzed by the acidic Cs salt of tungstophosphoric heteropoly acid, Cs2.5H0.5PW12O40, gives much rarer polycyclic oxygenated sesquiterpenes with a clovane structure. Cloven-9-ol and clovan-2,9-diol can be obtained with up to 80% combined selectivity and 60% individual selectivity each (under different reaction conditions). The process is environmentally benign and can be performed not only in conventional solvents such as 1,2-dichloroethane and acetone but also in eco-friendly green organic solvents such as dimethylcarbonate, diethylcarbonate and 2-methyltetrahydrofuran. The reactions occur under ambient conditions at low catalyst loadings without catalyst leaching. The solid catalyst can be simply centrifuged from the reaction mixture. Florol is a non-natural, floral odorant handled in the industry as a racemic diastereoisomeric mixture which can be used in a large number of fragrances and formulations conferring floral scents without changing the olfactory character of the perfume. In this work, Florol was synthesized using 20% H3PW12O40/SiO2 and Cs2,5H0,5PW12O40 as heterogeneous catalysts with 70-80% yield and high turnover numbers (TON). The process can be performed in environment-friendly green organic solvents, such as dimethylcarbonate, diethylcarbonate and 2-methyltetrahydrofuran. The reactions occur with small catalyst amounts without leaching problems. The CsPW can be removed by simple centrifugation, and then reutilized.